Effects of personalized depression prevention on anxiety through 18-month follow-up: A randomized controlled trial. (September 2022) - Jones, Jason D.; Hankin, Benjamin L.; Gallop, Robert; Haraden, Dustin; Sbrilli, Marissa D.; Garber, Judy; Young, Jami F.
Abstract: Depression and anxiety frequently co-occur and share several risk factors. There is some evidence for transdiagnostic effects of prevention programs on depression and anxiety. In the Personalized Depression Prevention (PDP) study, youth (n = 98, M age = 13.94 years, SD = 1.67) were classified as high or low on cognitive and interpersonal risk factors and randomized to either a cognitive-behavioral or an interpersonal prevention program. Some participants received a match between risk and prevention, others received a mismatch. Our initial work found evidence for the benefits of personalization on depression outcomes. In this paper, we focus on secondary anxiety outcomes through 18-months post-intervention. We found evidence for the benefits of personalized prevention on anxiety symptoms during the 18-month follow-up period, but not during the intervention. From post-intervention to 18-month follow-up matched youth showed a decrease in anxiety symptoms whereas mismatched youth showed a significant increase in symptoms ( d = 0.87, p = .001). The rates of anxiety disorders were equivalent across the groups ( p = 1.00). Given the comorbidity of depression and anxiety, interventions that have effects on both may be an efficient and cost-effective approach to reducing the burden associated with these conditions. A risk-informed personalization approach to prevention may be one way to enhance the transdiagnostic effects of depression prevention. Highlights: Depression and anxiety frequently co-occur and share several risk factors. Mixed evidence for transdiagnostic effects of depression prevention on anxiety. Youth were matched and mismatched to prevention programs based on risk profiles. Matched youth showed greater reductions in anxiety symptoms during follow-up. Risk-based personalization may enhance transdiagnostic effects of depression prevention.